"A Myth Becomes Reality": Kaspar Hauser as Messianic Wild Child - Ulrich Struve (Studies in 20th & 21st Century Literature, 1998)
The topos of the "Wild Child" occupies an important place in the mythic and literary imagination of the West. The European climax of a long line of wild children, Kaspar Hauser was a nineteenth-century German foundling whose fate has inspired a host of novels, dramas, novellas, poems, songs, and movies, even an opera and a ballet. It has been treated by Paul Verlaine, R. M. Rilke, and Klaus Mann, by the Dada poet Hans Arp, by the dramatist Peter Handke, and by the filmmaker Werner Herzog. This article offers a brief historical sketch of Hauser's life before discussing a key aspect of the literary Kaspar Hauser reception: the motif of the foundling as a latter-day messiah. By examining a set of twentieth-century texts that develop this motif in an exemplary manner—Jakob Wassermann's novel Caspar Hauser or The Inertia of the Heart, Georg Trakl's Kaspar Hauser Song, the anthroposophist Kaspar Hauser poems by Emma Krell-Werth, and David Constantine's Caspar Hauser: A Poem in Nine Cantos—we can gain insight into our century's desire for redemption and its ethical ramifications.
Keywords: Wild Child; mythic; literary imagination; West; European; wild children; Kaspar Hauser; nineteenth-century; German; foundling; Paul Verlaine; R. M. Rilke; Klaus Mann; Dada poet; Hans Arp; dramatist; Peter Handke; filmmaker; Werner Herzog; history; Hauser' s life; literary Kaspar Hauser; reception; latter-day messiah; Jakob Wassermann' s novel; Caspar Hauser; The Inertia of the Heart; Georg Trakl; Kaspar Hauser Song; poems; Emma Krell-Werth; David Constantine; Caspar Hauser: A Poem in Nine Cantos; desire for redemption; redemption; ethics